2006
DOI: 10.1111/j.1600-0420.2006.00707.x
|View full text |Cite
|
Sign up to set email alerts
|

NIKE: a new clinical tool for establishing levels of indications for cataract surgery

Abstract: ABSTRACT.Purpose: The purpose of this study was to construct a new clinical tool for establishing levels of indications for cataract surgery, and to validate this tool. Methods: Teams from nine eye clinics reached an agreement about the need to develop a clinical tool for setting levels of indications for cataract surgery and about the items that should be included in the tool. The tool was to be called 'NIKE' (Nationell Indikationsmodell fo¨r Kataraktextraktion). The Canadian Cataract Priority Criteria Tool s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
50
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 12 publications
0
50
0
1
Order By: Relevance
“…In particular, the Preferred Practice Guideline of the American Academy of Ophthalmology 1 and the RAND Appropriateness Methodology 2 both emphasize the importance of assessing visual function when determining the need for cataract surgery, while other guidelines were based on expert advice. 3,4 In China, a widely accepted criterion for cataract surgery is that the best-corrected visual acuity (BCVA) of the patient is lower than 20/40. 5 However, there are always a proportion of cataract patients who have good preoperative visual acuity but complain of poor vision.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the Preferred Practice Guideline of the American Academy of Ophthalmology 1 and the RAND Appropriateness Methodology 2 both emphasize the importance of assessing visual function when determining the need for cataract surgery, while other guidelines were based on expert advice. 3,4 In China, a widely accepted criterion for cataract surgery is that the best-corrected visual acuity (BCVA) of the patient is lower than 20/40. 5 However, there are always a proportion of cataract patients who have good preoperative visual acuity but complain of poor vision.…”
Section: Introductionmentioning
confidence: 99%
“…22 The questionnaire was self-administered, but the examiner was available to answer patients' queries in relation to any of the questionnaire items. A copy of the items in the Priquest questionnaire is given in Table 1.…”
Section: Subjective Visual Difficultymentioning
confidence: 99%
“…17 Consequently, it has been suggested that VA is not the most appropriate tool to investigate the impact of symptomatic non-advanced cataract on visual function and experience, 11 and complementary and/or alternative techniques that have been investigated include CS, 18 glare disability (GD), 19 reading performance, 20 and functional visual difficulty assessed by various questionnaires. [21][22][23] Morphological and optical characteristics of lens opacification are also important, and can be assessed by various grading systems 24 and Scheimpflug photography, 25,26 respectively, and have the advantage of being independent of patient cooperation and ocular co-morbidity.…”
Section: Introductionmentioning
confidence: 99%
“…12 Rasch analysis was applied to the questionnaire data using commercial software (WINSTEPS Rasch measurement computer program, version 3.70.0.2; Beaverton, Oregon [http://www.Winsteps.com]), thus calibrating item difficulty and patient ability on the same scale. 34,35 We found a significant gain in precision after Rasch scaling of the questionnaire (a gain of 32% and a relative precision of 1.32), thus reinforcing the current evidence with respect to the benefits of subjecting questionnaires to Rasch scaling.…”
Section: Subjective Visual Functioningmentioning
confidence: 99%